The international monetary system: structure, development and prospects / Zakarya Ahmad - Ahmad, Zakarya (Research Management Institude, 2003)
This research attempts to explore the evolution, issues and concerns of the present international monetary system. Looking at the previous literatures of the American Economic Association reveals that in almost every year, highlight on the agenda has been the question of reform. Interest in reform has increased in recent years, due to succession of crises that began with the European exchange rate mechanism (ERM) crisis of 1992- 93 and continued with the “tequila” crisis of 1994-95 and also the Asian, Russian, Long-Term Capital Management (LTCM), and Brazilian crises. This research examines the daily fluctuations between exchange rates and stock prices for five major currencies, including Deutschmark, US Dollar, Japanese Yen, Great Britain Pound and Singapore Dollar, for the period of February 1998 to October 2001. In doing so, the Aumented-Dickey Fuller test and Johansen procedure are applied to investigate the stationary and cointegration properties of the variables. Our empirical results show the one-way causality effect from the exchange rate on the equity market. Our results also suggest that fluctuations of the Ringgit against Deutschmark tend to exhibit significant influence on the equity index, regardless of the exchange rate arrangement system employed and the degree of capital controls.